Respon Mahasiswa terhadap e-Modul Etnofisika pada Materi Pengukuran - Eveline, Erlin (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2026)
The problem with learning today is that it is often irrelevant to students’ needs and characteristics. This study aims to identify students’ responses to an ethnophysics e-module on measurement material. The researcher analyzed students’ responses before and after the introduction of the e-module. The research method used was quantitative descriptive. Data were analyzed using descriptive techniques, focusing on the categories of availability of teaching materials, student participation and understanding, integration of the ethnophysics context (Maluku region), responsiveness to student needs, material comprehensibility, and student motivation and engagement. The sample in this study consisted of 10 university students from the Physics Education study program studying measurement concepts in the Basic Physics course. The results of the study showed a positive response to the developed e-module. Students stated that the e-module was responsive to the needs, easy to understand, and encouraged motivation and engagement in learning. Several students’ suggestions and opinions were used as a reference point for improving the developed module. Based on the research results, the development of teaching materials should consider the characteristics, needs, and relevance of the material to students’ environment and experiences. Keywords: students’ responses, teaching material, e-module, measurement, ethnophysics